2015
DOI: 10.1016/j.biopsych.2014.12.021
|View full text |Cite
|
Sign up to set email alerts
|

Neurobiological Impact of Nicotinic Acetylcholine Receptor Agonists: An Activation Likelihood Estimation Meta-Analysis of Pharmacologic Neuroimaging Studies

Abstract: Background Nicotinic acetylcholine receptor (nAChR) agonists augment cognition among cigarette smokers and nonsmokers, yet the systems-level neurobiological mechanisms underlying such improvements are not fully understood. Aggregating neuroimaging results regarding nAChR agonists provides a means to identify common functional brain changes that may be related to pro-cognitive drug effects. Methods We conducted a meta-analysis of pharmacological neuroimaging studies within the activation likelihood estimation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
50
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(54 citation statements)
references
References 83 publications
(99 reference statements)
3
50
0
1
Order By: Relevance
“…Since this study used simultaneous fMRI/EEG, the authors were able to correlate the functional connectivity of the default-mode network (by fMRI) with an objective measure of sedation (by EEG). Taking the fMRI studies together, the nicotine-induced decrease in the default-mode network activity found by Sutherland et al [60] indicates a possible nicotine-induced increase of vigilance. Anticipating our discussion, our EEG results suggest that nicotine does increase the neural signature of vigilance.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since this study used simultaneous fMRI/EEG, the authors were able to correlate the functional connectivity of the default-mode network (by fMRI) with an objective measure of sedation (by EEG). Taking the fMRI studies together, the nicotine-induced decrease in the default-mode network activity found by Sutherland et al [60] indicates a possible nicotine-induced increase of vigilance. Anticipating our discussion, our EEG results suggest that nicotine does increase the neural signature of vigilance.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, a meta-analysis of brain imaging data regarding nicotine appeared recently [60]. Although the authors did not specifically assess vigilance, they observed that nicotine decreases the activity in the default-mode network (a resting-state network), while increasing task-related brain regions.…”
Section: Discussionmentioning
confidence: 99%
“…Nicotinic acetylcholinergic receptors are widely distributed throughout the brain [36,37]. Smoking activates both the prefrontal cortex (BA9) and ACC (BA24) [38,39]. It is possible that the reduced pan (total) SNAP-25 BA9/BA24 ratio reflects smoking-induced alteration of the brain's acetylcholinergic distribution.…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, Rasmusson et al (2007) found that inactivation of prefrontal cortex inhibited sensory-evoked acetylcholine release in somatosensory cortex. In a meta-analysis of effects on neuroimaging, Sutherland et al (2015) concluded that nicotinic acetylcholine agonists reduce default-mode network activity and enhance executive control network regions. The basal forebrain thus appears to be an important efferent for the cortical regulation of the activity of central networks.…”
Section: Attentionmentioning
confidence: 99%